The Power Of Love For Survival In Sidney Sheldon's Rage Angels: An Individual Psychological Approach - Ristiananingrum, Dessy (2004)
This study focuses on the power of love for survival on the major character personality in Sidney Sheldon's Rage of Angels by using individual psychological approach. The objectives of the study are to analyze the structural elements of this novel and to analyze the novel based on the individual psychological perspective. This research employs a qualitative study. In this method, the researcher uses two data sources: primary and secondary data sources. Primary data source is the novel it self and secondary data includes any material related to the study. The method of data collecting is library research, and technique of analysis is descriptive. Based on the analysis, the researcher draw a conclusion as follows; the first, the major character's personality with her problems between love, death, duty, moral and law. The second, The power of Love Influences her survival in her life. The third, The Power of Love changes her life.